Dinamika Perkembangan Kewenangan Mahkamah Konstitusi - Umar, Kusnadi; Sofyan, Sofyan (Jurnal Al Tasyri'iyyah, 2023)
The Constitutional Court as the guardian of the constitution has a central role in a constitutional-democratic state. This study aims to reveal the extent of the development of the authority of the Constitutional Court in the constitutional system using a normative juridical approach. The results showed that the Constitutional Court experienced a "growth" of authority born from interpretations as an effort to renew and complement its constitutional authority. There are some powers that are not explicitly attributed to the 1945 NRI Constitution, but in practice, judges of the Constitutional Court interpret them to legitimize the basis of their authority. as in Perppu testing (formal and material), settlement of authority disputes between state institutions whose authority is delegative and settlement of disputes over regional head elections. The move confirms the inclusiveness of Constitutional Court judges on the dynamics of developments and legal needs in resolving every constitutional issue even though it is not stipulated in the Constitution and also as an effort and commitment to protect the constitutional rights of citizens.